A Rapid and Specific Assay for the Detection of MERS-CoV - Huang, Pei; Wang, Hualei; Cao, Zengguo; Jin, Hongli; Chi, Hang; Zhao, Jincun; Yu, Beibei; Yan, Feihu; Hu, Xingxing; Wu, Fangfang; Jiao, Cuicui; Hou, Pengfei; et al. (Frontiers in Microbiology, 2018)
Middle East respiratory syndrome coronavirus (MERS-CoV) is a novel human coronavirus that can cause human respiratory disease. The development of a detection method for this virus that can lead to rapid and accurate diagnosis would be significant. In this study, we established a nucleic acid visualization technique that combines the reverse transcription loop-mediated isothermal amplification technique and a vertical flow visualization strip (RT-LAMP-VF) to detect the N gene of MERS-CoV. The RT-LAMP-VF assay was performed in a constant temperature water bath for 30 min, and the result was visible by the naked eye within 2 min. The RT-LAMP-VF assay was capable of detecting 2×101 copies/µl of synthesized RNA transcript and 1×101copies/µl of MERS-CoV RNA. The method exhibits no cross-reactivities with multiple CoVs including SARS-related (SARSr)-CoV, HKU4, HKU1, OC43 and 229E, and thus exhibits high specificity. Compared to the real-time RT-PCR (rRT-PCR) method recommended by the World Health Organization (WHO)，the RT-LAMP-VF assay is easy to handle, does not require expensive equipment and can rapidly complete detection within 35 min.